FEATURES OF PURINE METABOLISM AND MICROALBUMINURIA OF ISCHEMIC HEART DISEASE IN PATIENTS WITH METABOLIC SYNDROME (World Bulletin of Public Health, 2024)
To study the state of purine metabolism and microalbuminuria in patients with metabolic syndrome